Ketahanan Pangan dalam Al-Qur’an: Telaah Konseptual Tafsir Maqāṣidī Ayat-Ayat Pangan - Muhammad Ainul Mukmin; Muhammad Izzul Fahmi; Mohammad Fajar Iskandar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Food security is still a global and national issue, including in Indonesia, which is characterized by uneven access to food, increased vulnerability of low-income groups, and ecological pressure on production resources. Al-Qur'an gives great attention to food issues not only as a fulfillment of biological needs, but also as part of the moral, economic, and ecological order. This research aims to explain the concept of food security in Al-Qur'an through a thematic interpretation approach (mawḍū'ī) through the framework of Maqāṣid Syariah by studying verses related to availability, access-distribution, and ecological balance, including al-Baqarah: 168, al-Insān: 8–9, al-Baqarah: 261, al-A'rāf: 31, and ar-Raḥmān: 7–9. The results of the study show that the concept of food security Al-Qur'an is built on three main principles in Maqāṣid Syariah: life protection (ḥifẓ al-nafs) through food availability, wealth protection (ḥifẓ al-māl) through access-distribution, and environmental protection (ḥifẓ al-bī'ah) through efforts to preserve the food production ecosystem. This study offers a holistic Al-Qur'an-based conceptual model of food security and can be an academic contribution to the study of thematic interpretation, Islamic economics, and contemporary food security.